2019
DOI: 10.15275/rusomj.2019.0201
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial interstitial matrix as novel target for succinic acid treatment strategies during experimental hypobaric hypoxia

Abstract: Objective -Quantitative morphological studies of myocardial cellular elements. Aim of research is to study myocardial interstitial matrix with and without succinic acid treatment in the rats exposed to intermittent hypobaric hypoxia.Material and Methods -The study was conducted on 26 adult males of Wistar rats weighing 220-310 g, divided into 3 groups. The first control group consisted of 6 intact animals. The second group included 10 rats which were exposed to hypobaric hypoxia without medication for 30 days.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Analysis of researches by other scientists re-vealed that using such components as humic acids, glauconite and succinic acids positively influences the digestibility of fodder (Hall, 1952), improves digestibility of minerals in the animals' intestine (Filipova, 2019) and when combined with minerals substances they improve productive parameters (tendency towards increase in weight in rabbits and higher coefficient of fodder conversion) and meat quality (increase in iron content in meat) (Mista & Rzasa, 2012;Maha et al, 2019). Zadnipryany et al (2019) determined a positive effect of succinic acid on supporting the contraction function of the cardiac muscle. Raafat (2011) revealed that dimercaptosuccinic acid (DMSA) is effective in reducing the intoxication impact of plumbum on the organism of rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of researches by other scientists re-vealed that using such components as humic acids, glauconite and succinic acids positively influences the digestibility of fodder (Hall, 1952), improves digestibility of minerals in the animals' intestine (Filipova, 2019) and when combined with minerals substances they improve productive parameters (tendency towards increase in weight in rabbits and higher coefficient of fodder conversion) and meat quality (increase in iron content in meat) (Mista & Rzasa, 2012;Maha et al, 2019). Zadnipryany et al (2019) determined a positive effect of succinic acid on supporting the contraction function of the cardiac muscle. Raafat (2011) revealed that dimercaptosuccinic acid (DMSA) is effective in reducing the intoxication impact of plumbum on the organism of rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, hypobaric hypoxia causes fibrosis in the myocardium, which inevitably leads to systolic and diastolic dysfunctions, neurohormonal activation and, finally, heart failure. At the same time, succinic acid combined with inosine functions acts as a highly-effective reserve of phosphate, which can support the level of adenosine triphosphate at the level sufficient for the support of the contractile function of the heart (Zadnipryany et al, 2019).…”
Section: Introductionmentioning
confidence: 99%